Factors driving Climate-Smart Agriculture adoption: a study of smallholder farmers in Koumpentum, Senegal - Ewulo, Taiwo A.; Akinseye, Folorunso M.; Teme, Niaba; Agele, Samuel O.; Yessoufou, Nouroudine; Kumar, Shalander (Frontiers in Agronomy, 2025)
Climate change significantly threatens agriculture and food systems in developing countries, especially in Senegal, where agriculture is vital for livelihoods and economic advancement. A study investigated the factors influencing the adoption of Climate-Smart Agriculture (CSA) innovations among smallholder farmers in Koumpentum, Senegal. Through comprehensive research and multistage random sampling, 270 smallholder farmers were interviewed using structured questionnaires. The results indicated that 56.3% of the farmers have adopted CSA practices. Household size, perceived climate change, and access to climate advisory information positively influenced 70.4% of farmers to adopt crop rotation. Additionally, the farmer's experience (in years) and perception of climate change influenced the adoption of conservation tillage. The study highlights how smallholder-specific characteristics and external influences interact to determine CSA adoption. Moreover, it underscores the need for targeted interventions to promote CSA practices, emphasizing the importance of farmer education, access to climate advisory services, and capacity building. Based on our findings, the policy recommendations include aligning CSA innovations with smallholder preferences and local conditions to enhance adoption rates and strengthen climate resilience in agricultural systems. Policymakers should integrate CSA into Senegalese agricultural policy and develop innovative financing mechanisms to encourage the adoption of adaptation technologies tailored to local contexts to address current and future climate risks.